Keseimbangan Kehidupan Kerja dan Lingkungan Kerja sebagai Determinan Kepuasan Kerja: Studi pada Asisten Apoteker di Rumah Sakit Provinsi di Nusa Tenggara Barat - Muhammad Ari At-Thoriq; Wahyulina, Sri; Fauzi, Armi Sulthon (Universitas Muhammadiyah Pontianak, 2026)
This reseach analyzes the effect of Work–Life Balance and Work Environment on Job Satisfaction within 78 pharmacy assistants at the Provincial General Hospital of West Nusa Tenggara using a quantitative associative method. Data were obtained using structured survey forms and processed with multivariate linear analysis. Findings show that both variables significantly affect Job Satisfaction, with Work Environment having a stronger impact. Validity, reliability, and classical assumption tests were met. The findings emphasize the need for conducive workplace settings and regulations that encourage work–life balance to enhance worker satisfaction and strengthen healthcare service quality.